Reconstruction of a source term in a parabolic integro-differential equation from final data - Kasemets, Kairi; Janno, Jaan (Mathematical Modelling and Analysis, 2011)
The identification of a source term in a parabolic integro-differential equation is considered. We study the existence of the quasi-solution to this problem, Tikhonov regularization and a related gradient method.